Sex Hormones, BDNF, Leptin, and TGF-β1 in Females With IBS: A Pilot Investigation. Issue 2 (April 2021) - Weaver, Kristen R.; Boulineaux, Christina M.; Robinson, Jeffrey M.; Butler, Kierra; Heitkemper, Margaret M.; Henderson, Wendy A.
Background: Irritable bowel syndrome (IBS) is a chronic gastrointestinal condition predominantly affecting the female sex, and is characterized by brain-gut axis dysregulation. Relevance of hormones along the hypothalamic-pituitary gonadal axis and hypothalamic-pituitary adrenal axis to IBS symptomatology remain unclear, as does the significance of other modulators including brain derived neurotrophic factor (BDNF), leptin, and transforming growth factor βeta 1 (TGF-β1). Methods: Females with IBS were compared with female healthy controls (HC) on age, race, hormonal contraceptive use, body mass index, adrenocorticotropic hormone, cortisol, estradiol, follicular stimulating hormone, luteinizing hormone, progesterone, total cholesterol, Center for Epidemiological Studies Depression Scale (CES-D) and Perceived Stress Scale (PSS). BDNF, leptin, and TGF-β1 were quantified using enzyme-linked immunosorbent assay. Descriptive statistics, non-parametric techniques, and regression analyses were performed. Results: Participants with IBS (n = 12) displayed higher estradiol ( p = .027) than did HC (n = 21). Direction of associations among study variables often differed between groups: BDNF and progesterone in HC (rs = .623) and in IBS (rs = −.723). The relationship between log (CES-D) and log (estradiol) varied by IBS status (interaction term p = 0.019). Discussion: Elevated estradiol in participants with IBS, and differential patterns of biological and psychological indices between groups, encourages further inquiry on the relevance of sex hormones, BDNF, leptin, and TGF-β1 to symptoms of IBS. Future research endeavors should conduct longitudinal quantification of sex hormones with subjective symptom assessment to facilitate insight on the pathophysiology and female sex bias in IBS.